JENIS-JENIS SERANGGA NOCTURNAL PADA TANAMAN DUKU (Lansium domesticum Corr.) DI DESA SRIGENI LAMA KABUPATEN OKI PROVINSI SUMATERA SELATAN - Dian Mutiara (Universitas PGRI Palembang, 2015)
The research about identification insects at duku (Lansium domesticum Corr.) plantation was conducted at Serigeni Lama Kayuagung village on September till October 2014. The objective of this research was collect insects at duku. This research utilited the direct observation method during two moon. This method used insecting net, light traps and fit fall traps. The result of the identification geted 7 Order, 14 Family, 15 Genera, dan 15 Spesies. Key words : Identification, insects, Lansium domesticum Corr